2019
DOI: 10.1242/dmm.041103
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the titin/MURF1 signaling complex is associated with hypertrophic cardiomyopathy in a fish model and in human patients

Abstract: Hypertrophic cardiomyopathy (HCM) is a hereditary disease characterized by cardiac hypertrophy with diastolic dysfunction. Gene mutations causing HCM have been found in about half of HCM patients, while the genetic etiology and pathogenesis remain unknown for many cases of HCM. To identify novel mechanisms underlying HCM pathogenesis, we generated a cardiovascular-mutant medaka fish, non-spring heart (nsh), which showed diastolic dysfunction and hypertrophic myocardium. The nsh homozygotes had fewer myofibrils… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Moreover, very recent data showed that missense mutations in a titin Ig domain located in the M line-A-band transition zone of titin disrupted sarcomeres and led to HCM both in medaka fish and in humans [181]. In vitro studies revealed that these mutations increased the binding of MuRF1 [181].…”
Section: Other Murf1 Interactors (Not or Not Yet Substrates)mentioning
confidence: 99%
“…Moreover, very recent data showed that missense mutations in a titin Ig domain located in the M line-A-band transition zone of titin disrupted sarcomeres and led to HCM both in medaka fish and in humans [181]. In vitro studies revealed that these mutations increased the binding of MuRF1 [181].…”
Section: Other Murf1 Interactors (Not or Not Yet Substrates)mentioning
confidence: 99%
“…While not rare in some forms of HCM, restrictive phenotype had a malign prognosis in pediatric and adult patients with HCM ( Maskatia et al, 2012 ; Li et al, 2020 ). In TRIM63 -associated HCM, restrictive dysfunction could reflect the altered molecular interaction of MuRF1 with titin ( Higashikuse et al, 2019 ). There is a MuRF1-binding site in titin adjacent to the titin kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…There is a MuRF1-binding site in titin adjacent to the titin kinase domain. Mutations of this region lead to hypertrophy and diastolic dysfunction in the medaka fish experimental model and Japanese patients with HCM associated with TRIM63 ( Higashikuse et al, 2019 ). In addition, mutations of the titin MuRF1-binding site lead to the expression shift to the stiffer titin isoforms, increased titin binding to MuRF1, and enhanced titin degradation through ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Titin and titin-related molecules were found to be important in the intersection of myocardial stiffness and HCM. Higashikuse et al (2019) suggested that titin mutations in HCM families can be incorporated into the sarcomere and impair TRIM63 (MURF1) binding, resulting in abnormal sarcomere stiffness [ 60 ].…”
Section: Discussionmentioning
confidence: 99%